Properties of Hardened Concrete Containing CBA Ash and FCS as Partial Sand Replacement - Khalid, F S; Zahir, Z; Shahidan, S (International Journal of Sustainable Construction Engineering and Technology, 2020)
A large amount of coal bottom ash (CBA) is being discharged from thermal power plants and has been making serious environmental pollution. Meanwhile, fine coconut shell (FCS) is an agricultural waste and is available in plentiful quantities throughout tropical countries worldwide. In many countries, coconut shell is subjected to open burning which contributes significantly to CO2 and methane emissions. Both of these materials are essential to utilize the CBA and FCS to reduce environmental pollution. Therefore, this study aims to determine the properties of combination of these materials as partial sand replacement. CBA is slow in pozzolanic activity of coal bottom ash which is suitable for partial replacement sand. Meanwhile, FCS is lightweight material with high density in porous filler. Concrete designed for 30 MPa strength at 28 days curing age and 0.50 of water-cement ratio in this study. The percentage of CBA used is 5%, 10%, 15% and 20%, while the percentage of FCS is 2%, 4%, 6% and 8% where it has been replaced by volume replacement. The specimens were cured in water for 7, 28, 56 and 90 days curing ages before compressive and splitting tensile strength test are conducted. It can be concluded that the density of the concrete decreased, compressive and splitting tensile strength show the improvement with the utilization of CBA and FCS in concrete. In addition, the percentage of water absorption increased as both of CBA and FCS absorb the water. This study shows that an optimum percentage of CBA found is 10% and FCS is 6% for this study.